Santa Maria degli Angeli: un monastero camaldolese "dimenticato" nel centro di Firenze Analisi del percorso storico-architettonico in età moderna e contemporanea - RICCI, CHIARA (Premio Tesi di Dottorato, 2021)
The topic of this publication is the Camaldolese monastery of Santa Maria degli Angeli, located in the historic center of Florence, in an area between via degli Alfani, via del Castellaccio and piazza Brunelleschi. The study of the religious complex, founded in 1295, was tackled with the dual purpose to reconstruct the historical-architectural events of the last four centuries and to identify the causes of the fractionation following its suppression in 1866. The fractionation between different properties resulted in the current loss of architectural legibility of the Camaldolese monastery; for this reason one of the most important religious and cultural centers of the Florentine fourteenth-fifteenth century was almost "forgotten" not only by the citizens, but also by historiography.